Magnetotelluric surveys of the Mae Chan and Fang geothermal systems, Thailand - Puwis Amatyakul (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The magnetotelluric (MT) surveys were conducted on Mae Chan geothermal field in Chiang Rai province and Fang geothermal field in Chiang Mai province for geothermal energy assessment. Both areas were classified as the key areas for further development. The acquired MT data were inverted using a 3-D MT inversion to construct the 3-D resistivity model revealing the geothermal system up to the depth of 4 km. The results from both areas indicate the conductive bodies that situates less than 100 m up to 750 m depth. Those conductive bodies are interpreted as hot fluid reservoirs in weathered granite beneath the overlying sedimentary deposit. The deep resistive zone is corresponding to the batholith granite heat source while the resistivity contrast corresponded to the Mae Chan Fault (MCF) and it associated fault system. The results are used to delineate the geothermal system of the two areas. Further investigation, including the extended MT survey and test drilling, is proposed for the deeper conductive bodies as the possible geothermal reservoirs. The results will be used in geothermal assessment integrating with other exploration methods to further investigate the true potential of both areas.